2020
DOI: 10.3386/w26920
|View full text |Cite
|
Sign up to set email alerts
|

What Explains the Gender Gap in Wealth? Evidence from Administrative Data

Abstract: This paper studies the gender gap in net wealth. We use administrative data on wealth that are linked to the Estonian Household Finance and Consumption Survey, which provides individual-level wealth data for all household types. We find that the unconditional gender gap in mean wealth is 45% and that it is caused by large wealth disparities in the upper end of the wealth distribution. The structure of assets owned by men is more diversified than that for women. Men own more business assets and vehicles, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…The results differ not because there is less inequality in France but because Bonnet et al (2013) did not include business assets in their study, whereas in Germany the biggest wealth gap was observed in business wealth. These results are in line with D'Alessio (2018), who found 18% gender wealth gap in Italy, and Meriküll et al (2018), who estimated approximately 45% gender wealth gap in Estonia, the country with the largest gender wage gap in EU. Furthermore, Meriküll, et al (2018) showed that the gender wealth gap is the largest in self-employment business wealth.…”
Section: Related Literaturesupporting
confidence: 90%
See 4 more Smart Citations
“…The results differ not because there is less inequality in France but because Bonnet et al (2013) did not include business assets in their study, whereas in Germany the biggest wealth gap was observed in business wealth. These results are in line with D'Alessio (2018), who found 18% gender wealth gap in Italy, and Meriküll et al (2018), who estimated approximately 45% gender wealth gap in Estonia, the country with the largest gender wage gap in EU. Furthermore, Meriküll, et al (2018) showed that the gender wealth gap is the largest in self-employment business wealth.…”
Section: Related Literaturesupporting
confidence: 90%
“…These results are in line with D'Alessio (2018), who found 18% gender wealth gap in Italy, and Meriküll et al (2018), who estimated approximately 45% gender wealth gap in Estonia, the country with the largest gender wage gap in EU. Furthermore, Meriküll, et al (2018) showed that the gender wealth gap is the largest in self-employment business wealth.…”
Section: Related Literaturesupporting
confidence: 90%
See 3 more Smart Citations